A Review of Ayurvedic Principles and the use of Ayurvedic Plants to Control Diarrhoea and Gastrointestinal Infections - Tiwana, Gagan; Cock, Ian Edwin; Cheesman, Matthew James (Pharmacognosy Communications)
According to the World Health Organisation (WHO), diarrhoea is the second leading cause of death in children under the age of five. It is a common symptom associated with gastrointestinal bacterial infections. Many antibiotics have lost their efficacy due to the rapid emergence of Antimicrobial Resistant (AMR) bacterial pathogens. Traditional Ayurvedic medicinal plants are likely to play a significant role in the development of new effective and safe therapies in the fight against AMR in gastrointestinal bacteria. Recent research has reported the effectiveness of numerous different Ayurvedic medicines in the treatment of gastrointestinal infections. One example is Triphala, which is a polyherbal formulation consisting of an equal mixture of dried fruit powders from the three Ayurvedic plants Terminalia bellirica (Gaertn.) Roxb., Terminalia chebula Retz. and Emblica officinalis Linn. This review discusses the principles of Ayurveda and summarises the traditional use of Ayurvedic plants in the treatment of diarrhoea, dysentery, and stomach discomfort.
Keywords: Ayurvedic plants; Traditional medicine; Anti-microbial resistance; Gastrointestinal; Diarrhoea; Polyherbal formulation; Toxicity; Phytochemicals.